Exploring The Effectiveness Of Safety Interventions For Reducing Road Crash Occurrence in Different Road Environments - Acharya, Nitesh; Henry, Michael (Journal on Transportation System and Engineering, 2025)
Despite a recent decline in annual crash fatalities, road safety remains a global issue with significant challenges. Road safety management focuses on analyzing causes and identifying effective ways to mitigate crashes. Among other components of the road environment, safety features and interventions can be improved to enhance safety. This study aims to evaluate the effectiveness of safety interventions in reducing crash occurrence and severity within similar road environments. The condition of the existing safety interventions was assessed along with the types of crashes occurring in certain road environments, and the results showed unique relationships between the same interventions and crash types in different road environments. Such information can be useful for road agencies to plan their safety improvement programs.Factor analysis on mixed data, Data clustering, Decision tree